2022
DOI: 10.3390/diagnostics12071595
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear and Linear Measures in the Differentiation of Postural Control in Patients after Total Hip or Knee Replacement and Healthy Controls

Abstract: Primary osteoarthritis treatments such as a total hip (THR) or knee (TKR) replacement lead to postural control changes reinforced by age. Balance tests such as standing with eyes open (EO) or closed (EC) give a possibility to calculate both linear and nonlinear indicators. This study aimed to find the group of linear and/or nonlinear measures that can differentiate healthy people and patients with TKR or THR from each other. This study enrolled 49 THR patients, 53 TKR patients, and 16 healthy controls. The cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…With an understanding of how ApEn and velocity of COP behave for varying levels of stability in neurotypical subjects, these indices may be useful to screen for conditions such as concussion in a more objective manner. Linear and nonlinear measures have been previously used in studies to determine changes to stability based on different neurological and physical impairments [46,47]. Although these studies compared a baseline control group to a group with impaired postural control as opposed to comparing a baseline condition of an individual to adjusted conditions of the same individual and utilized a different quiet standing methodology than this study, the clinical application of these measures on COP to distinguish postural control encourages the motivation for this work.…”
Section: Discussionmentioning
confidence: 99%
“…With an understanding of how ApEn and velocity of COP behave for varying levels of stability in neurotypical subjects, these indices may be useful to screen for conditions such as concussion in a more objective manner. Linear and nonlinear measures have been previously used in studies to determine changes to stability based on different neurological and physical impairments [46,47]. Although these studies compared a baseline control group to a group with impaired postural control as opposed to comparing a baseline condition of an individual to adjusted conditions of the same individual and utilized a different quiet standing methodology than this study, the clinical application of these measures on COP to distinguish postural control encourages the motivation for this work.…”
Section: Discussionmentioning
confidence: 99%
“…considered two features that capture signal complexity: Approximate Entropy (ApEn) [28], and Lyapunov Exponent (LyExp) [22], [29].…”
Section: A Data Processing For Postural Sway Parametersmentioning
confidence: 99%
“…To address these challenges, studies have shown that postural sway can be assessed using data from just a sacral accelerometer [16], [20], [21]. Sacral sensor-derived postural sway measures have been used to classify fall risk in PwMS [20], distinguish between disease states [16], [19], [22] and to augment current assessment techniques [23], thereby achieving similar clinical utility to the force platform.…”
Section: Introductionmentioning
confidence: 99%
“…These features included thirteen features from Mancini et al [16]: Jerk, Distance (Dist), Root-Mean-Square (RMS), Path, Range, Mean Velocity (MV), Mean Frequency (MF), Area, Power (Pwr), median power frequency (F50), 95% power frequency (F95), Centroidal Frequency (CF), and Frequency Dispersion (FD). We also considered two features that capture signal complexity: Approximate Entropy (ApEn) [28], and Lyapunov Exponent (LyExp) [22], [29]. Process overview of subject specific distribution (SSD) and a 30-second single observation (SO) methods.…”
Section: A Data Processing For Postural Sway Parametersmentioning
confidence: 99%